Use of medium cut-off membrane dialyzer compared to high flux membrane dialyzer in improving the clearance of middle to large molecule uremic toxins: A Systematic Review - Wasal Desrial Siregar; Krisna Yetti; Agung Waluyo; yulia yulia (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: The loss of kidney function in patients with kidney disease leads to the accumulation of dissolved substances known as uremic toxins, which can negatively impact patient health. Membranes with a high number of pores, such as those in high-flux dialyzers, allow some medium-sized molecules like beta-2 microglobulin to pass through. However, these membranes are less effective at filtering out larger dissolved substances. Larger medium-sized molecules (>25 kD) need to be removed either by convection or through the use of highly permeable membranes such as Medium Cut-Off (MCO) membranes. Therefore, it is important to understand the improvement in uremic toxin clearance when using MCO dialyzers compared to high-flux dialyzers. Purpose: To evaluate and compare the effectiveness of using medium cut-off (MCO) membrane dialyzer with high flux membrane dialyzer. Method: A systematic review with article selection guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The systematic review process begins with the formulation of clinical questions relevant to the topic. Before this, the authors establish PICOS criteria, which stand for: P (problem, patient, or population), I (intervention, prognostic factor, or exposure), C (comparison or control), O (outcome), and S (study design). For this article, P: Patients with chronic kidney disease undergoing hemodialysis, I: Use of dialyzers with medium cut-off (MCO) membrane, C: Use of dialyzer with high flux membrane, O: Increased clearance of uremic toxins of middle to large molecules, such as β2-microglobulin, kappa and lambda free light chains, S: Randomized controlled trials. The article search was conducted systematically using the keywords: